Negotiating Islam: A Study on the Debus Fatwa of the Indonesian Council of Ulama in Banten - Rohman, Rohman (Islamic Studies Review, 2023)
Unlike most works which study and focus on discussing fatwa (religious edicts) produced by the Indonesian Council of Ulama (Majelis Ulama Indonesia, MUI) at the central level, I focus on one of the fatwas produced by MUI at the regional level. In this article, I examine a fatwa on debus (a traditional martial arts performance that is imbued with supernatural powers) issued by the provincial MUI branch in Banten during a regional meeting involving all MUI branches from Java and Lampung, held in August 2009 in Serang City, Banten. Based on the data collected from key informants and internet research, including contemporary analysis, I argue that although fatwas are non-binding, a fatwa can also be negotiated based on the political, social, and cultural circumstances of a region. In other words, the power and influence of religious authority can be mitigated when it collides with the interests of a powerful group in a society. I also argue that MUI branches at the regional level are closely linked to the national MUI office’s policies and interests in upholding Islamic conservatism in Indonesia. This article provides further analysis dealing with religious authority in the Indonesian context, highlighting once again that this authority is never monolithic or absolute.